KEDUDUKAN ANCAMAN PIDANA MINIMAL DALAM UNDANG- UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA PASCA DIKELUARKANNYA SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2015 - Iswahyuni, Ari (Jurnal Panorama Hukum, 2018)
The problem of narcotics abuse and illicit trafficking in Indonesia shows an increasing trend, already very alarming and endangering the lives of people, society and nations. It is necessary to prevent and eradicate the abuse and illicit trafficking of narcotics in Indonesia, which includes a comprehensive multi-dimensional synergistic effort, to achieve maximum results. This effort is carried out gradually, consistently and continuously until it reaches the condition of Indonesia which is free from abuse and illicit narcotics trafficking even though still found a challenge and many obstacles related law enforcement Indonesia. Some cases illustrate the difficulty of law enforcers / practitioner looking for ways to make laws appear in line with community norms. This is addressed by the Supreme Court as a judicial body by issuing legal products in the form of Circular Letter of the Supreme Court (SEMA) Number 3 - Year 2015, with the aim of filling a legal void. However, this step leads to confusion and legal uncertainty because the contents of the SEMA are contrary to Law No. 35 of 2009 about Narcotics.